Implementation of the Design Thinking Method in the UI/UX Design of the Bellina Studio Website - Sinta Putri, Destya Ayu; Nugroho, Adi (Sistemasi: Jurnal Sistem Informasi, 2025)
The rapid growth of the beauty industry demands effective digital marketing strategies, including optimal website UI/UX design. This study explores the UI/UX design of the Bellina Studio website using the Design Thinking method to enhance user experience. The main issues identified include difficulties faced by customers in accessing service information, making reservations, and finding nail art references and promotional offers. The objective of this study is to design a more intuitive and efficient UI/UX interface to support Bellina Studio’s marketing strategy. The Design Thinking method was implemented through five stages: Empathize, Define, Ideate, Prototype, and Test. Usability evaluation was conducted using the System Usability Scale (SUS) on 105 respondents. The results show that the developed UI/UX design significantly improved user satisfaction and ease of access, achieving a SUS score of 82 from general users and 85 from expert users, both categorized as “excellent usability.” By applying the Design Thinking approach, this study aims to deliver an innovative, user-centered solution relevant to the digital beauty industry.